2017
DOI: 10.1590/1414-431x20165711
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes between off-pump versus on-pump coronary artery bypass surgery in elderly patients: a meta-analysis

Abstract: The aim of this study was to analyze if off-pump coronary artery bypass surgery (CABG) is associated with better treatment outcomes in elderly patients (>70 years of age) than on-pump CABG, using meta-analysis. Medline, PubMed, Cochrane and Google Scholar databases were searched until September 13, 2016. Sensitivity and quality assessment were performed. Twenty-two studies, three randomized control trials (RCTs) and 20 non-RCTs were included with 24,127 patients. The risk of death associated with on-pump or of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…The results of this study were in line with Z.G. Zhu et al revealed that the patients undergoing on-pump CABG surgery had longer length of hospital stay compared with the cases undergoing off-pump CABG surgery (P=0.001) (18).…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study were in line with Z.G. Zhu et al revealed that the patients undergoing on-pump CABG surgery had longer length of hospital stay compared with the cases undergoing off-pump CABG surgery (P=0.001) (18).…”
Section: Discussionsupporting
confidence: 90%
“…off-pump CABG in patients with age of >70 or >80 years. The results are contradictory, e.g ., Altarabsheh et al [ 11 ] found higher rates of stroke following on-pump surgery, whilst Panesar et al [ 12 ] and Zhu et al [ 13 ] found comparable rates. Although elderly people represent an important subset of patients, there is a much broader age range of patients undergoing on- or off-pump CABG.…”
Section: Introductionmentioning
confidence: 99%
“…It may be time, however, to focus on identifying which patients benefit from which procedure, i.e., offpump CABG is probably better for some patients and on-pump CABG for others (9). For example, off- pump CABG may be superior for elderly patients (10), octogenarians (11), and patients with chronic kidney disease (CKD) (12). First, in a meta-analysis (10) of 3 RCTs and 20 non-RCTs with a total of 12,697 ≥70-year patients, there was a reduced chance of overall mortality (from 30-day to 10-year follow-up) in patients who received off-pump CABG compared with on-pump CABG (pooled OR, 0.744; 95% CI, 0.587-0.944; P=0.015).…”
Section: Editorialmentioning
confidence: 99%